Perceived emotional states mediate willingness to buy from advertising speech - Nagano, Mizuki; Ijima, Yusuke; Hiroya, Sadao (Frontiers in Psychology, 2023)
Previous studies have shown that stimulus-organism-response (SOR) theory can well explain the willingness to buy from stores, products, and advertising-related stimuli. However, few studies have investigated advertising speech stimulus that is not influenced by visual design. We examined whether SOR theory using emotional states can explain the willingness to buy from advertising speech stimulus. Participants listened to speech with modified speech features (mean F0, speech rate, and standard deviation of F0) and rated their willingness to buy the advertised products and their perceived emotional states (pleasure, arousal, dominance). We found that emotional states partially mediate the influence of speech features on the willingness to buy. We further analyzed the moderating effects of listeners' attributes and found that listeners' gender and age group moderated the relationship between speech features, emotional states, and willingness to buy. These results indicate that perceived emotional states mediate the willingness to buy from advertising speech.